Nexus between Entrepreneurial Stimulation and Business Start-up in Nigeria - Mary E. EZEMA; Omotayo A. ADEGBUYI; Felicia O. OLOKOYO; Stanley N. AJALIE (Communications of International Proceedings, 2021)
Starting a business is generating great solutions to high rate of unemployment problem and also the unutilised resources throughout the economies. By so doing, start-ups have taken a great impact and task in the growth of economic strategies and policies of all countries over the globe. Notwithstanding the significance of start-ups, their evolution and inspiration behind them are yet to be fully investigated. Therefore, this study examines the motivation behind the business start-ups among graduates/trainees of three selected FBOs entrepreneurship programmes. The study carried out a survey on the 620 trainees that have started their business, to fine out their motives. The data were subjected to relevant statistical analysis, including descriptive statistics using SPSS version 25. Out of the 620 respondents 195(31.5%) of the respondents noted that desire for achievement motivated them to start their businesses. Also 167(26.9%) of the respondents started their business because of the availability of opportunity. This is an indication that people are motivated to start business when there is a desirable outcome. Availability of opportunities attracts individuals to try their hands on something. Government should make the environment conducive for business and make laws that are favourable to creating opportunities.
Keywords: Business Start-Up; Entrepreneurial Stimulation; Entrepreneurship; Faith-Based Entrepreneurship Trainings; Nigeria